Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2141.2011.08973.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet apoptosis in paediatric immune thrombocytopenia is ameliorated by intravenous immunoglobulin

Abstract: SummaryTo evaluate the role of intravenous immunoglobulin (IVIg) in platelet apoptosis in paediatric immune thrombocytopenia, we investigated the platelets of 20 paediatric patients with acute immune thrombocytopenia (ITP), before and after IVIg treatment. Healthy children with platelet counts in the normal range and children with thrombocytopenia due to chemotherapy were enrolled as controls. All ITP patients presented with platelet counts <20 · 10 9 /l and bleeding symptoms. Markers of apoptosis, including a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 37 publications
7
63
1
3
Order By: Relevance
“…Platelet apoptosis plays an important role in platelet clearance from the circulation, thus determines the life span of platelets. Enhanced platelet apoptosis has been implicated in a number of pathological processes, such as type 2 diabetes [7], immune thrombocytopenia [8], Bernard-Soulier syndrome [9] and thrombocytopenic purpura induced by Helicobacter pylori [10] or malaria [11].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet apoptosis plays an important role in platelet clearance from the circulation, thus determines the life span of platelets. Enhanced platelet apoptosis has been implicated in a number of pathological processes, such as type 2 diabetes [7], immune thrombocytopenia [8], Bernard-Soulier syndrome [9] and thrombocytopenic purpura induced by Helicobacter pylori [10] or malaria [11].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from inhibition of MK differentiation and platelet formation, anti-platelet antibody appears to induce apoptosis of platelets, which may be another factor contributing to the immunopathology of ITP 23,26,35 . Anti-platelet autoantibody has been shown to increase mitochondrial inner membrane potential (∆ ψ m ) depolarization, caspase-3,8,9 activation and phosphatidylserine exposure in platelets 23,35 , indicating a mitochondrion-dependent apoptosis pathway involved.…”
Section: Discussionmentioning
confidence: 99%
“…Gammagard could also have reduced apoptosis of the neuroblastoma cells, which has been observed in neurons exposed to α-synuclein [29]. IVIG products have been reported to exert anti-apoptotic effects in some systems [57][58][59] but not in others [60,61]. Studies in an animal model of synucleinopathy are indicated to determine if IVIG will exert neuroprotective effects in vivo.…”
Section: Discussionmentioning
confidence: 99%